(untitled) (Jurnal Teknologi (Sciences & Engineering), 2025)
X-ray medical imaging serves as a cornerstone in diagnostic procedures, offering essential insights into anatomical structures conditions. The optimization of image quality and patient safety in x-ray imaging is carried out by using appropriate filtration for x-ray beam. This paper presents a comparative analysis of aluminium (Al), copper (Cu) filters and combination of both materials for evaluating the effectiveness in attenuating low-energy photons and minimizing patient radiation exposure while maintaining image quality. This study investigates the TOR CDR phantom as an object with the exposure factor of 70 kV and 5 mAs, examining variations in thickness and filter materials to evaluate low and high contrast imaging procedures. The obtained dose values are compared with Signal-to-Noise Ratio (SNR) as well as Contrast-to-Noise Ratio (CNR) values, which represent the quality of the image to evaluate the impact of filtration on diagnostic image quality. The results indicate that for low contrast imaging a 5 mm Al filter is recommended, where it increases the SNR value by 41.3%, the dose decreases by 65.4%, but it may reduce the contrast by 31.7%. Meanwhile, for the high contrast imaging the recommended filter variation is 0.1 mm Al and 1 mm Cu. It can increase the SNR value by 52.7%, the dose decreases by 55.4%, but it may reduce CNR by 6.7%.